Polymer Resins for Dielectric Applications
The arylcyclobutene and allyl ether resin composition addresses the limitations of existing polymer resins by enhancing mechanical and dielectric properties and enabling faster, lower-temperature curing, suitable for electronic applications.
Patent Information
- Application Number
- JP2023074784
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2043-04-28
AI Technical Summary
Existing polymer resins used in electronic applications lack optimal mechanical properties, adhesion to copper, and dielectric performance, particularly at high frequencies, and require excessive cure times and temperatures.
A resin composition comprising 60-90% arylcyclobutene resin and 10-40% allyl ether resin, which is cured through copolymerization of addition-polymerizable monomers, providing improved mechanical strength, adhesion, and low dielectric properties, with the ability to cure at lower temperatures.
The composition achieves high tensile strength, good adhesion to copper, low dielectric constant, and loss tangent, while allowing for faster and more efficient curing processes.
Smart Images

Figure 0007614249000001 
Figure 0007614249000002 
Figure 0007614249000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to polymeric resin compositions, methods for preparing such resins and their use in manufacturing electronic devices. [Background technology]
[0002] Polymer resins are used in spin-on dielectric packaging, circuit boards, laminates, and other electronic applications. These resins must provide films / coatings with good mechanical and adhesive properties, as well as low dielectric properties. In particular, it is desirable to have high tensile strength, high tensile elongation, good adhesion to copper, and low dielectric constant (Dk) and loss tangent (Df) at high frequencies. In addition, it is desirable to be able to cure the resins at lower temperatures without excessive cure times. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] U.S. Patent No. 7,198,878 [Patent Document 2] U.S. Patent No. 8,143,360 [Patent Document 3] US Patent Application Publication No. 20190169327A1 [Patent Document 4] U.S. Patent No. 10,030,165B2 Summary of the Invention [Means for solving the problem]
[0004] There is a continuing need for dielectric resin compositions with improved properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0005] As used throughout this specification, the following abbreviations shall have the following meanings unless the context clearly indicates otherwise: °C = degrees Celsius; g = grams; nm = nanometers, μm = microns = micrometers; mm = millimeters; sec. = seconds; and min. = minutes. Unless otherwise specified, all amounts are weight percent ("wt %") and all ratios are molar ratios. All numerical ranges are inclusive and combinable in any order, except where it is clear that such numerical ranges are constrained to add up to 100%. Unless otherwise specified, all polymer and oligomer molecular weights are weight average molecular weights ("Mw") in g / mole or Daltons, measured using gel permeation chromatography relative to polystyrene standards.
[0006] The articles "a," "an," and "the" refer to the singular and plural unless the context clearly indicates otherwise. As used herein, the term "and / or" includes any and all combinations of one or more of the associated items.
[0007] As used herein, R, R a , R b , R', R'', and any other variables are generic and may be the same or different from the variables defined in the formula.
[0008] As used herein, the term "addition polymerizable" as it applies to monomers is intended to mean unsaturated monomers that can be polymerized by the simple linkage of groups without the concomitant formation of other products.
[0009] The term "adjacent," when referring to substituents, is intended to mean substituents that are attached to linked carbons by a single or multiple bond. Exemplary adjacent R groups are shown below: [ka]
[0010] The term "alkoxy" is intended to mean the group RO--, where R is an alkyl group.
[0011] The term "alkyl" is intended to mean a group derived from an aliphatic hydrocarbon, and includes straight-chain, branched, or cyclic groups. A group "derived from" a compound refers to a radical formed by removal of one or more hydrogens or deuteriums. In some embodiments, an alkyl has 1 to 20 carbon atoms.
[0012] The term "aromatic compound" is intended to mean an organic compound containing at least one unsaturated cyclic group having 4n+2 delocalized π-electrons.
[0013] The term "aryl" is intended to mean a group derived from an aromatic compound with one or more points of attachment. The term includes groups having a single ring as well as groups having multiple rings that can be linked by a single bond or fused together. Carbocyclic aryl groups have only carbon in the ring structure. Heteroaryl groups have at least one heteroatom in the ring structure.
[0014] The term "alkylaryl" is intended to mean an aryl group having one or more alkyl substituents.
[0015] The term "aryloxy" is intended to mean the group RO-, where R is an aryl group.
[0016] The term "curable" as applied to a composition is intended to mean a material that becomes harder and less soluble in solvents when exposed to radiation and / or heat, or under conditions of use.
[0017] The term "liquid composition" is intended to mean a liquid medium in which a material is dissolved to form a solution, a liquid medium in which a material is dispersed to form a dispersion, or a liquid medium in which a material is suspended to form a suspension or emulsion.
[0018] The term "(meth)acrylate" is intended to mean a group that is either an acrylate or a methacrylate.
[0019] The term "solvent" is intended to mean an organic compound that is liquid at the room temperature of use. The term is intended to encompass a single organic compound or a mixture of two or more organic compounds.
[0020] The terms "film" and "layer" are used interchangeably throughout this specification.
[0021] All ranges are inclusive and combinable, for example, the term "in the range of 50-3000 cPs, or 100 cPs or more" would include each of 50-100 cPs, 50-3000 cPs, and 100-3000 cPs.
[0022] Unless otherwise expressly stated herein or unless indicated to the contrary in connection with the use, when an embodiment of the subject matter herein is stated or described as comprising, including, containing, containing, having, consisting of, or composed of a particular feature or element, one or more features or elements in addition to those expressly stated or described may be present in the embodiment. An alternative embodiment of the subject matter disclosed herein may be stated as consisting essentially of a particular feature or element, but in that embodiment, no feature or element is present therein that materially alters the principle of operation or distinguishing characteristics of the embodiment. A further alternative embodiment of the subject matter described herein may be stated as consisting of a particular feature or element, but in that embodiment or in an intangible variation thereof, only the feature or element specifically stated or described is present.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of embodiments of the present disclosure, suitable methods and materials are described below. Furthermore, the materials, methods, and examples are illustrative only and are not intended to be limiting.
[0024] To the extent not described herein, many details regarding specific materials, processing operations, and circuits are conventional and can be found in textbooks and other sources in the photoresist, dielectric materials, and semiconductor component art.
[0025] (a) 60 to 90% by weight of at least one thermosetting resin; and (b) 10 to 40% by weight of at least one Allyl The resin composition is provided from a mixture including the ether resin.
[0026] The thermosetting resin is not particularly limited and is selected from the group consisting of arylcyclobutenes, vinyl radical cured polymers, bismaleimide thermosetting resins, epoxy thermosetting resins, and thermosetting resins cured by Michael addition.
[0027] The arylcyclobutene resin comprises a polymerization product from a mixture containing: (a) 10 to 50 mol % of one or more addition-polymerizable arylcyclobutene monomers; and (b) 15 to 60 mol % of one or more dienophile monomers, (c) 15 to 50 mol % of one or more diene monomers, and (d) 0 to 10 mol % of one or more heterocycle-containing monomers.
[0028] The arylcyclobutene resins are prepared from addition polymerizable arylcyclobutene monomers, which are arylcyclobutenes having at least one addition polymerizable substituent. The substituent can be a vinyl group, an allyl group, or a (meth)acrylate group. The monomer can be present in an amount of 10 to 50 mole percent, or in some embodiments, 20 to 40 mole percent, based on the total monomers present in the copolymerization.
[0029] In some embodiments, the arylcyclobutene monomer has Formula A-1, Formula A-2, or Formula A-3, shown below: [ka]
[0030] In formula A-1, K 1 can be a divalent group selected from the group consisting of alkyl, aryl, carbocyclic aryl, polycyclic aryl, heteroaryl, aryloxy, arylalkyl, carbonyl, ester, carboxyl, ether, thioester, thioether, tertiary amine, and combinations thereof. In some non-limiting embodiments, K 1 is an unsubstituted C with no heteroatoms. 6~36 Carbocyclic aryl group or unsubstituted C with no heteroatoms 6~18 a carbocyclic aryl group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 6~36 A carbocyclic aryl group or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy. 6~18 Carbocyclic aryl group; or unsubstituted C 3~36 Heteroaryl group or unsubstituted C 3~18 heteroaryl group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 6~36 A substituted C having at least one substituent selected from the group consisting of a heteroaryl group, an alkyl group, and an alkoxy group. 6~18 Heteroaryl group; or unsubstituted C6~36 Unsubstituted C with no aryloxy group or ring heteroatom 6~18 an aryloxy group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 3~36 A substituted C having at least one substituent selected from the group consisting of a heteroaryloxy group, an alkyl group, and an alkoxy group. 3~18 Heteroaryloxy group; or unsubstituted C 6~36 Arylalkyl group or unsubstituted C with no heteroatoms 6~18 arylalkyl groups; or substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 3~36 Heteroarylalkyl groups or substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy. 3~18 It may be a heteroarylalkyl group.
[0031] In formula A-1, L 1 is a covalent bond or a polyvalent linking group. In some non-limiting embodiments, L 1 C has no ring heteroatoms 6~12 It is a carbocyclic aryl group or is selected from the group consisting of phenyl, biphenyl, and naphthyl.
[0032] In formula A-1, M is a substituted or unsubstituted divalent aromatic or polycyclic aromatic radical group, or a substituted or unsubstituted divalent heteroaromatic or polycyclic heteroaromatic radical group. In some non-limiting embodiments of formula A-1, M is an unsubstituted C 6~36 Carbocyclic aryl group or unsubstituted C with no heteroatoms 6~18 a carbocyclic aryl group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 6~36 A carbocyclic aryl group or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy. 6~18 Carbocyclic aryl group; or unsubstituted C 3~36 Heteroaryl group or unsubstituted C3~18 heteroaryl group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 6~36 A substituted C having at least one substituent selected from the group consisting of a heteroaryl group, an alkyl group, and an alkoxy group. 6~18 It is a heteroaryl group.
[0033] In formula A-1, R 5 is selected from the group consisting of hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkyloxy, substituted or unsubstituted aryl, substituted or unsubstituted aryloxy, alkylthio, arylthiol, substituted alkylamino, and substituted arylamino. In some non-limiting embodiments of Formula A-1, R 5 is hydrogen; or C 1~6 Alkyl or C 1~3 Alkyl; or C 1~6 Alkoxy or C 1~3 It is an alkoxy.
[0034] In formula A-1, R 6 and R 7 are the same or different and are independently selected from the group consisting of hydrogen, deuterium, cyano, halo, methyl, vinyl, allyl, and substituted or unsubstituted isoprene having 1 to 100 carbon atoms.
[0035] In some non-limiting embodiments of Formula A-1, R 5 =R 6 =R 7 = Hydrogen.
[0036] In some non-limiting embodiments of Formula A-1, x and y are the same or different and are integers from 1 to 5; L 1 If is a covalent bond, then y=1.
[0037] In formula A-2, K 2can be a single bond or a divalent group selected from the group consisting of alkyl, aryl, carbocyclic aryl, polycyclic aryl, heteroaryl, aryloxy, arylalkyl, carbonyl, ester, carboxyl, and ether, thioester, thioether, tertiary amine, and combinations thereof. In some non-limiting embodiments, K 2 is a covalent bond; or an unsubstituted C 6~36 Carbocyclic aryl group or unsubstituted C with no heteroatoms 6~18 a carbocyclic aryl group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 6~36 A carbocyclic aryl group or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy. 6~18 Carbocyclic aryl group; or unsubstituted C 3~36 Heteroaryl group or unsubstituted C 3~18 heteroaryl; or substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 6~36 A substituted C having at least one substituent selected from the group consisting of a heteroaryl group, an alkyl group, and an alkoxy group. 6~18 Heteroaryl group; or unsubstituted C 6~36 Unsubstituted C with no aryloxy group or ring heteroatom 6~18 an aryloxy group; or a substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 3~36 A substituted C having at least one substituent selected from the group consisting of a heteroaryloxy group, an alkyl group, and an alkoxy group. 3~18 Heteroaryloxy group; or unsubstituted C 6~36 Arylalkyl group or unsubstituted C with no heteroatoms 6~18 arylalkyl groups; or substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy; 3~36 Heteroarylalkyl groups or substituted C having at least one substituent selected from the group consisting of alkyl and alkoxy.3~18 It may be a heteroarylalkyl group.
[0038] L in formula A-1 1 , M, x, and y are L in formula A-2 1 , M, x, and y. 5 All of the above embodiments for R in formula A-2 1 ~R 7 applies equally to
[0039] In formula A-3, K 3 is a polymerizable functional group selected from the group consisting of vinyl, styryl, maleimide, acryl, methacryl, allyl, alkynyl, or functional equivalents.
[0040] L in formulas A-1 and A-2 1 , M, x, and y are L in formula A-3 1 , M, x, and y. 1 ~R 4 All of the above embodiments for R in formula A-3 1 ~R 4 applies equally to
[0041] In one non-limiting embodiment, the arylcyclobutene monomer has the formula A-1-a: [ka] (In the formula, Ar is a substituted or unsubstituted carbocyclic aryl or a substituted or unsubstituted heteroaryl group; Q is a covalent bond, O, S, or NR a and R a is selected from the group consisting of hydrogen, deuterium, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl; R 5 ~R 7are the same or different and are independently selected from the group consisting of hydrogen, deuterium, alkyl, alkoxy, substituted or unsubstituted carbocyclic aryl groups, and substituted or unsubstituted heteroaryl groups; R 8 is selected from the group consisting of alkyl, alkoxy, a substituted or unsubstituted carbocyclic aryl group, and a substituted or unsubstituted heteroaryl group; and a is an integer of 0 to 4.
[0042] In formula A-1-a, Ar is an unsubstituted carbocyclic aryl group having 6 to 36 ring carbons, or an unsubstituted carbocyclic aryl group having 6 to 12 ring carbons; or a substituted carbocyclic aryl group having 6 to 36 ring carbons and having at least one substituent selected from the group consisting of alkyl and alkoxy, or a substituted carbocyclic aryl group having 6 to 12 ring carbons and having at least one substituent selected from the group consisting of alkyl and alkoxy; or a heteroaryl group having 3 to 36 ring carbons, or a heteroaryl group having 3 to 12 ring carbons; or a substituted heteroaryl group having 6 to 36 ring carbons and having at least one substituent selected from the group consisting of alkyl and alkoxy, or a substituted heteroaryl group having 3 to 12 ring carbons and having at least one substituent selected from the group consisting of alkyl and alkoxy; or is selected from the group consisting of phenyl, biphenyl, and naphthyl.
[0043] In some non-limiting embodiments of Formula A-1-a, Q is a covalent bond, or O, or S, or NH, or NCH 3 It is.
[0044] In some non-limiting embodiments of Formula A-1-a, a is 0; or 1; or 2; or >0; or >0, and at least one R 8 is C 1~6 Alkyl or C 1~3 alkyl; or >0; at least one R 8 is C 1~6 Alkoxy or C 1~3 It is an alkoxy.
[0045] In another non-limiting embodiment, the arylcyclobutene monomer has the formula A-2-a: [ka] (In the formula, Ar is a substituted or unsubstituted carbocyclic aryl or a substituted or unsubstituted heteroaryl group; Q is a covalent bond, O, S, or NR a ;R a is selected from the group consisting of hydrogen, deuterium, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl; R 1 ~R 7 are the same or different and are independently selected from the group consisting of hydrogen, deuterium, alkyl, alkoxy, aryloxy, substituted or unsubstituted carbocyclic aryl groups, and substituted or unsubstituted heteroaryl groups; R 8 is selected from the group consisting of alkyl, alkoxy, a substituted or unsubstituted carbocyclic aryl group, and a substituted or unsubstituted heteroaryl group; and b is an integer of 0 to 3.
[0046] In formula A-2-a, b can be 0; or 1; or 2; or >0; or >0, and at least one R 8 is C 1~6 Alkyl or C 1~3 alkyl; or >0; at least one R 8 is C 1~6 Alkoxy or C 1~3 It is an alkoxy.
[0047] All of the above embodiments for Ar and Q in formula A-1-a apply equally to Ar and Q in formula A-2-a. 5 All of the above embodiments for R in formula A-2-a 1 ~R 7 applies equally to
[0048] Examples of arylcyclobutene monomers can include, but are not limited to, 1-(4-vinylphenoxy)-benzocyclobutene, 1-(4-vinylmethoxy)-benzocyclobutene, 1-(4-vinylphenyl)-benzocyclobutene, 1-(4-vinylhydroxynaphthyl)-benzocyclobutene, 4-vinyl-1-methyl-benzocyclobutene, 4-vinyl-1-methoxy-benzocyclobutene, and 4-vinyl-1-phenoxy-benzocyclobutene.
[0049] The arylcyclobutene resins are prepared from one or more dienophile monomers present in an amount of 5 to 70 mole percent, or in some embodiments 15 to 60 mole percent, based on total monomers present in the copolymerization having a structure given by formula (II): [ka]
[0050] In formula (II), B can be hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted aromatic, substituted or unsubstituted heteroaromatic, substituted or unsubstituted alkyloxy, or hydroxy. 9 ~R 11 are the same or different and are independently selected from the group consisting of hydrogen, deuterium, methyl, vinyl, allyl, a substituted or unsubstituted isoprene having 1 to 100 carbon atoms, a substituted or unsubstituted alkyl group having 1 to 100 carbon atoms, halogen, cyano, a substituted or unsubstituted aryl group having 6 to 100 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 100 carbon atoms, and combinations thereof.
[0051] In some non-limiting embodiments, the one or more dienophile monomers have a structure given by formula (III): [ka] (In the formula, R 12 ~R 14are the same or different, hydrogen and C 1~5 alkyl; R 15 are the same or different in each occurrence and are hydrogen and C 1~5 alkyl, and adjacent R 15 The groups can be joined to form a fused six-membered aromatic ring.
[0052] In some non-limiting embodiments, the one or more dienophile monomers are selected from the group consisting of styrene, α-methylstyrene, vinyltoluene, 1-vinylnaphthalene, and 2-vinylnaphthalene.
[0053] The diene monomer may be present in an amount of 15 to 50 mole percent, 15 to 30 mole percent, or 20 to 25 mole percent based on the total monomers present in the copolymerization. In one embodiment, the diene monomer has formula (IV) shown below: [ka] (In the formula, R 16 is the same or different in each occurrence and is selected from the group consisting of hydrogen and methyl; R 17 are the same or different in each occurrence and are hydrogen, C 1~5 Alkyl, C 1~5 Alkoxy, C 1~5 Thioalkyl, and C 5~12 alkenyl).
[0054] In formula IV, R 16 can all be hydrogen, or three R 16 is hydrogen and one R 16 is methyl. Two R 17 are the same; or different; or at least one R 17 is hydrogen; or at least one R 17 is C 1~3 alkyl, or methyl; or at least one R 17 is C 1~3alkoxy, or methoxy; or at least one R 17 is a compound of the formula -(CH 2 ) c -CH=C(R 18 ) 2 (wherein c is an integer of 1 to 5; R 18 is hydrogen or methyl).
[0055] Examples of diene monomers can include, but are not limited to, butadiene, isoprene, 1,3-pentadiene, 2,4-hexadiene, cyclopentadiene, β-myrcene, ocimene, cyclooctadiene, farnesene, and polymerizable terpenes.
[0056] The mixture may comprise 1 to 20 mol %, or 3 to 10 mol %, or 4 to 7 mol % of an addition-polymerizable vinyl-substituted C 3~12 Heterocyclic or vinyl substituted C 3~5 In some embodiments, the heterocyclic monomer may further comprise one or more C 1~6 Alkyl, C 6~12 Carbocyclic aryl, or C 3~12 It may be further substituted with a heteroaryl. The heterocyclic monomer is selected from the group consisting of N-heterocycles, S-heterocycles, N,S-heterocycles, and substituted derivatives thereof.
[0057] N-heterocycles can have at least one ring nitrogen. Examples of N-heterocycles can include, but are not limited to, pyrrole, pyridine, diazine, triazine, imidazole, benzimidazole, and quinolone. S-heterocycles can have at least one ring sulfur. Examples of S-heterocycles can include, but are not limited to, thiophene, benzothiophene, and dibenzothiophene. N,S-heterocycles can have at least one ring nitrogen and one ring sulfur. Examples of N,S-heterocycles can include, but are not limited to, thiazole, thiadiazole, and thiadiazine.
[0058] In one non-limiting embodiment, the heterocyclic monomer has Formula V, shown below: [ka] (In the formula, Z 1 and Z 2 are the same or different, N or CR 22a ;R 19 ~R 21 and R 22a are the same or different in each occurrence and are hydrogen and C 1~5 alkyl).
[0059] In formula V, Z 1 =Z 2 or Z 1 ≠Z 2 or Z 1 is CH or CR 22a or N, or CH; or Z 2 CR 22a , or N. 19 is hydrogen or C 1~3 R in formula V is alkyl, or methyl. 19 All of the above embodiments for R in formula V 20 , R 21 , and R 22a or R 19 =R 20 =R 21 = Hydrogen.
[0060] Examples of heterocyclic monomers include, but are not limited to, 4-vinylpyridine, 4-vinyl-1,3-diazine, 2-vinyl-1,3,5-triazine, and 4-methyl-5-vinyl-1,3-thiazole. Additionally, one or more additional addition polymerizable monomers may be present in the polymerization.
[0061] In some non-limiting embodiments, the at least one arylcyclobutene resin has a structure given by formula (VI): [ka] (In the formula, Ar 1 is a heterocycle containing an N, S, O, or P atom; R 23 H, CH 3 , ethyl, or t-butyl; R 24 H, CH 3 , C 1 ~C 12 Alkyl or C 1 ~C 12 alkylene; R 25 is cyclobutene, 1-oxy-cyclobutene, or α-methylcyclobutene; l is an integer from 0 to 10; R 26 is an alkyl group, a cycloalkyl group, or an aryl group of 1 to 12 carbon atoms; n is an integer from 5 to 70; m is an integer from 5 to 50; o is an integer from 5 to 50; p is an integer from 5 to 50; so that l+n+m+o+p=100.
[0062] In some non-limiting embodiments, at least one Allyl The ether resin has a structure given by formula (VII) [ka] (In the formula, R 27 are the same or different at each occurrence and are selected from hydrogen, methyl, alkyl, aryl, and Ar-O-CH 2 -CH=CH 2 R 28 is the same or different at each occurrence and is hydrogen, amino, hydroxyl, allyl, -O-CH 2 -CH=CH 2 and alkyl; Ar is the same or different at each occurrence and is selected from the group consisting of benzyl, naphthyl, biphenyl, and bisphenol A; and n=1-10.
[0063] In some non-limiting embodiments, at least one AllylThe ether resin is present from 5 to 50 weight percent, in some non-limiting embodiments from 10 to 40 weight percent, and in some non-limiting embodiments from 15 to 25 weight percent of the resin composition.
[0064] In some non-limiting embodiments, at least one Allyl The ether resin has a molecular weight of less than 5,000 Da, in some non-limiting embodiments less than 4,000 Da, in some non-limiting embodiments less than 3,000 Da, in some non-limiting embodiments less than 2,000 Da, and in some non-limiting embodiments less than 1,000 Da.
[0065] In some non-limiting embodiments, the allyl ether resin having a structure given by formula (VII) is prepared from one or more copolymer-based precursors selected from the group consisting of phenol-benzaldehyde copolymer, phenol-formaldehyde copolymer, biphenyl / phenol-formaldehyde copolymer, bisphenol-A formaldehyde copolymer, cresol-formaldehyde copolymer, naphthalene / phenol-formaldehyde copolymer, and the like, and combinations thereof.
[0066] In some non-limiting embodiments, the precursor used may be one or more selected from the group consisting of a phenolic hardener having a novolac structure and a naphtholic hardener having a novolac structure. In some non-limiting embodiments, a phenolic novolac resin, a triazine skeleton-containing phenolic novolac resin, a naphthol novolac resin, a naphthol aralkyl type resin, a triazine skeleton-containing naphthol resin, and a biphenyl aralkyl type phenolic resin may be used. Commercially available biphenyl aralkyl type phenolic resins include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH7851-4H" (available from Meiwa Kasei Co., Ltd.) and "GPH" (available from Nippon Kayaku Co., Ltd.). Commercially available naphthol novolac resins include "NHN" and "CBN" (available from Nippon Kayaku Co., Ltd.). Commercially available naphthol aralkyl type resins include "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN395", and "SN375" (available from Tohto Kasei Co., Ltd.). Commercially available phenolic novolac resins include "TD2090" (available from DIC Corporation), and commercially available triazine skeleton-containing phenolic novolac resins include "LA3018", "LA7052", "LA7054", and "LAI356" (available from DIC Corporation). These resins may be used alone or in combination of two, three or more.
[0067] In some non-limiting embodiments, at least one Allyl The ether resin is selected from the group consisting of formulas (B1) to (B6) [ka] [ka] (wherein n=1 to 10).
[0068] The arylcyclobutene resins disclosed herein can be formed by copolymerizing the above addition polymerizable monomers through the action of a thermal initiator, photoinitiator, or other photoactive compound.
[0069] In one embodiment, the copolymerization process includes providing a mixture of addition polymerizable monomers as described above in a polar solvent and a radical initiator, and heating the mixture to a temperature of 50-150° C. for a period of 5-50 hours. In another embodiment, the copolymerization process includes providing a mixture of addition polymerizable monomers as described above in a polar solvent, heating the mixture to a temperature of 50-150° C. to form a heated mixture, and continuously feeding a radical initiator to the heated mixture for a period of 5-50 hours.
[0070] The polar solvent can be a single organic compound or a mixture of compounds. A polar solvent is one in which the monomers are miscible or dispersible. The polar solvent can be present in an amount of 10-70 wt%, or 20-50 wt%, based on the total weight of the reaction mixture. In one embodiment, the polar solvent is a (cyclo)alkanone or cyclic ester, or a linear or branched ketone and a C 1~8 It can be a polar organic solvent, such as an ester.
[0071] The radical initiator is generally an azo compound or an organic peroxide. In one embodiment, the radical initiator is an oil-soluble azo compound. Such initiators can include, for example, dimethyl 2,2'-azobis(2-methylpropionate) and 2,2'-azobis(2,4-dimethylvaleronitrile). The total initiator added can range from 1 to 5% by weight, based on the weight of the starting reaction mixture.
[0072] After the desired reaction time, the resulting final reaction mixture is obtained, cooled to room temperature (20-25° C.) and processed as necessary. The polymers of the present disclosure may be used as is or may be isolated by precipitating the polymer from solution by addition of a non-solvent, such as water or methanol, followed by removal of the organic solvent.
[0073] Disclosed herein Allyl Ether resins can be formed by reaction of phenol-aldehyde type copolymers with allyl halides. The phenol-aldehyde resins can be deprotonated with a suitable base, resulting in displacement to produce allyl ether products.
[0074] The present disclosure further relates to a liquid composition comprising the above resin dissolved or dispersed in one or more organic solvents. The liquid composition can be deposited onto a substrate using any known technique to form a film, and then heated to remove the solvent. This can be followed by an additional heating step to further harden the film. In some non-limiting embodiments, the liquid composition of the present disclosure can be used to form a dielectric film for bulk dielectric applications, such as in photolithography, packaging, adhesives, sealing, and spin-on coatings or buffer layers. The dielectric film formed on the substrate can be used directly or can be peeled off and then used on various substrates in electronic devices.
[0075] Any substrate known in the art can be used in the present disclosure, including, but not limited to, silicon, copper, silver, indium tin oxide, silicon dioxide, glass, silicon nitride, aluminum, gold, polyimide, and epoxy molding compound.
[0076] Suitable organic solvents are those in which the resin is soluble. Particularly useful organic solvents are any solvents useful for the preparation or formulation of arylcyclobutene polymers. Exemplary organic solvents include, without limitation, polar protic solvents and polar aprotic solvents, such as alcohols such as 2-methyl-1-butanol, 4-methyl-2-pentanol, and methyl isobutyl carbinol; esters such as ethyl lactate, propylene glycol methyl ether acetate, methyl 2-hydroxyisobutyrate, methyl 3-methoxypropionate, n-butyl acetate, and 3-methoxy-1-butyl acetate; lactones such as gamma-butyrolactone; lactams such as N-methylpyrrolidinone; ethers such as propylene glycol methyl ether and dipropylene glycol dimethyl ether isomers, such as PROGLYDE™ DMM (The Dow Chemical Company, Midland, MI); ketones such as 2-butanone, cyclopentanone, cyclohexanone, and methylcyclohexanone; and mixtures thereof.
[0077] Suitable additives can be added to the liquid compositions of the present disclosure. Examples of additives can include, without limitation, one or more of each of the following: curing agents, crosslinking agents, such as crosslinkable monomers separate from the polymer, surfactants, inorganic fillers, organic fillers, plasticizers, adhesion promoters, metal passivators, and combinations of any of the foregoing. Suitable surfactants are well known to those skilled in the art, with nonionic surfactants being preferred. Such surfactants can be present in an amount of 0-10 g / L, or 0-5 g / L.
[0078] Any suitable inorganic filler can be optionally used in the composition, and they are well known to those skilled in the art. Exemplary inorganic fillers can include, but are not limited to, silica, alumina, barium sulfate, talc, clay, mica powder, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum borate, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate, and calcium zirconate. In some non-limiting embodiments, the silica can be amorphous silica, ground silica, fumed silica, crystalline silica, synthetic silica, or hollow silica. In some non-limiting embodiments, spherical silica is used. The inorganic filler can be used alone or in combination of two or more. In some non-limiting embodiments, no inorganic filler is used.
[0079] The average particle size of the inorganic filler is not particularly limited. From the viewpoint of forming fine wiring on the insulating layer, the upper limit of the average particle size of the inorganic filler is 5 μm or less, in some non-limiting embodiments, 3 μm or less, in some non-limiting embodiments, 1 μm or less, in some non-limiting embodiments, 0.7 μm or less, in some non-limiting embodiments, 0.5 μm or less, in some non-limiting embodiments, 0.4 μm or less, and in some non-limiting embodiments, 0.3 μm or less. On the other hand, the lower limit of the average particle size of the inorganic filler can be 0.01 μm or more, in some non-limiting embodiments, 0.03 μm or more, in some non-limiting embodiments, 0.05 μm or more, in some non-limiting embodiments, 0.07 μm or more, and in some non-limiting embodiments, 0.1 μm or more.
[0080] The average particle size of the inorganic filler can be measured by laser diffraction and scattering methods based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is determined on a volume basis using a laser diffraction particle size distribution measuring device, and the median diameter can be measured as the average particle size. The measurement can be performed on a dispersion liquid in which the inorganic filler is dispersed in water by ultrasonic waves. The measurement can be performed using commercially available devices such as LA-500, 750, and 950 manufactured by Horiba, Ltd.
[0081] Inorganic fillers are typically used in amounts of 35% to 80% by weight, based on the total nonvolatile weight of the composition.
[0082] The inorganic filler may or may not be surface-treated with a coupling agent to make the filler compatible with the thermosetting resin. Those skilled in the art can understand how to select a surface treatment to match the appropriate thermosetting resin chemistry. Non-limiting examples of surface treatment agents include phenyltrimethoxysilane, methacryloxypropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, mercaptopropyltrimethoxysilane, hexamethyldisilazane, and diisopropoxytitaniumbis(triethanolamine).
[0083] The metal passivator can be a copper passivator. Suitable copper passivators are well known in the art and include imidazole, benzotriazole, ethylenediamine or its salts or acid esters, and iminodiacetic acid or its salts. Such crosslinkers are typically used in an amount of 0-5 wt.%, or 0.2-1 wt.%, based on the total weight of polymerizable monomers in the composition.
[0084] Any suitable crosslinking agent may be optionally used in the liquid composition. Suitable crosslinking agents may react with functional groups in the resin composition, such as alkenes and Diels-Alder dienes, as selected by one of ordinary skill in the art. Such suitable crosslinking agents may include polyfunctional thiols, polyfunctional azides, polyfunctional azirines, and bis-arylcyclobutene monomers, as well as polyfunctional dienophiles, such as (meth)acrylates, maleimides, allyl compounds, vinylsilane compounds, or other suitable dienophiles, provided that they crosslink the polymers of the present disclosure under the conditions used to cure the composition. The selection of such crosslinking agents is within the capabilities of one of ordinary skill in the art. Such crosslinking agents are typically used in amounts of 0-30% by weight, or 0-15% by weight, based on the total weight of polymerizable monomers in the composition.
[0085] A variety of curing agents can be used in the liquid compositions of the present disclosure that are useful for photolithography. Suitable curing agents can aid in the curing of bis-benzocyclobutene-containing materials and can be activated by heat or light. Exemplary curing agents can include, but are not limited to, thermally generated initiators and photoactive compounds (photogenerated initiators). The selection of such curing agents is within the capabilities of one skilled in the art. Preferred thermally generated initiators are free radical initiators, such as, but not limited to, azobisisobutyronitrile, dibenzoyl peroxide, and dicumyl peroxide. Preferred photoactive curing agents are free radical photoinitiators available from BASF under the Irgacure brand, and diazonaphthoquinone (DNQ) compounds, including sulfonate esters of DNQ compounds. Suitable DNQ compounds are any compounds that have a DNQ moiety, such as a DNQ sulfonate ester moiety, and function as a photoactive compound in the present compositions, i.e., they function as a dissolution initiator upon exposure to appropriate radiation. Suitable DNQ compounds are disclosed in US Pat. No. 5,399,623 and US Pat. No. 5,499,623, the entire contents of which are incorporated herein by reference.
[0086] The amount of photoactive compound varies from 0 to 30% by weight, based on the total weight of polymer solids. When present, photoactive compounds are typically used in amounts of 5 to 30%, or 5 to 25%, or 10 to 25% by weight, based on the total weight of polymer solids.
[0087] Any suitable adhesion promoter may be used in the liquid composition of the present disclosure, and the selection of such an adhesion promoter is well within the capabilities of one skilled in the art. In some non-limiting examples, the adhesion promoter is a silane-containing material or a tetraalkyl titanate, or a trialkoxysilane-containing material. Exemplary adhesion promoters include, but are not limited to, bis(trialkoxysilylalkyl)benzenes such as bis(trimethoxysilylethyl)benzene; aminoalkyltrialkoxysilanes such as aminopropyltrimethoxysilane, aminopropyltriethoxysilane, and phenylaminopropyltriethoxysilane; and other silane coupling agents, as well as mixtures of the foregoing. The adhesion promoter may be applied first as a primer layer or as an additive to the composition. Particularly suitable adhesion promoters include AP3000, AP8000, and AP9000C (DuPont de Nemours, Wilmington, DE). The liquid composition of the present disclosure may contain from 0 to 15 wt%, or from 0.5 to 10 wt%, or from 1 to 10 wt%, or from 2 to 10 wt%, of the adhesion promoter, based on the total weight of the composition.
[0088] Any suitable softener and plasticizer can be used in the liquid composition of the present disclosure, the selection of which is well within the capabilities of one skilled in the art. Examples of softeners include, but are not limited to, BMI689 (Designer Molecules), diallyl phthalate and isomers, hexanediol diacrylate, and other suitable materials that are liquid at a temperature of 25° C. Softeners are used at 0-20% by weight, or 2-10% by weight, or 3-5% by weight of the total weight of the nonvolatile content of the composition.
[0089] Any suitable flame retardant can be used in the liquid composition of the present disclosure, and its selection is well within the capabilities of those skilled in the art. Examples of flame retardants include organic phosphorus flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, silicone flame retardants, and metal hydroxides. The organic phosphorus flame retardant may be a phosphorus compound of the phenanthrene type, such as HCA, HCA-HQ, and HCA-NQ (Sanko Co., Ltd.); a phosphorus-containing benzoxazine compound, such as HFB-2006M (Showa Polymer Co., Ltd.); a phosphorus ester compound, such as REOFOS30, 50, 65, 90, 110, TPP, RPD, BAPP, CPD, TCP, TXP, TBP, TOP, KP140, and TIBP (Ajinomoto Fine-Techno Co., Ltd.), TPPO and PPQ (Hokuko Chemical Industry Co., Ltd.), OP930 (Clariant Ltd.), and PX200 (Daihachi Chemical Industry Co., Ltd.); a phosphorus-containing epoxy resin, such as FX289, FX305, and TX0712 (Tohto Kasei Co., Ltd.); a phosphorus-containing phenoxy resin, such as ERF001 (Tohto Kasei Co., Ltd.); and a phosphorus-containing epoxy resin, such as YL7613 (Nippon Epoxy Resin Manufacturing Co., Ltd.).
[0090] The organic nitrogen-containing phosphorus compound may be a phosphoric acid ester amide compound such as SP670 and SP703 (Shikoku Chemical Industry Co., Ltd.); a phosphazene compound such as SPB-100, SPV-100, and SPE-100 (Otsuka Chemical Co., Ltd.); and an FP series (Fushimi Pharmaceutical Co., Ltd.). The metal hydroxide may be magnesium hydroxide such as UD65, UD650, and UD653 (Ube Materials Corporation); and aluminum hydroxide such as B-30, B-325, B-315, B-308, B-303, and UFH-20 (Tomoe Engineering Co., Ltd.).
[0091] In some non-limiting embodiments, the content of the flame retardant is 0.5 to 10% by weight, and in some non-limiting embodiments, 1 to 5% by weight, based on 100% by weight of the nonvolatile components in the resin composition.
[0092] Any suitable surface leveling agent or "leveling agent" can be used in the liquid compositions of the present disclosure, the selection of which is well within the capabilities of one of ordinary skill in the art. The leveling agent may be any of the following monomers, Si(R 1 )(R 2 )(OR 3 ) 2 (In the formula, R 1 , R 2 or R 3 is C 1 ~C 20 Alkyl or C 5 ~C 20 Aliphatic group or C 1 ~C 20 The leveling agent may contain many silicone units derived from the polymerization of aryl groups (each independently selected from the group consisting of aryl groups). In one non-limiting embodiment, the leveling agent is non-ionic and may contain at least two functional groups that can chemically react with functional groups contained in the silicon and non-silicone resins under cationic photocuring process or thermal curing conditions. Leveling agents containing non-reactive groups are present in some non-limiting embodiments. In addition to silicon-derived units, the leveling agent may contain C groups containing oxirane rings. 3 ~C 20 The leveling agent may contain units derived from the polymerization of aliphatic molecules. In addition, the leveling agent may contain C 1 ~C 50 It may include units derived from aliphatic molecules. In some non-limiting embodiments, the leveling agent does not include halogen substituents. In some non-limiting embodiments, the molecular structure of the leveling agent is predominantly linear, branched, or hyperbranched, or it may be a graft structure.
[0093] In some non-limiting embodiments; the leveling agent is AD1700, MD700; Megaface F-114, F-251, F-253, F-281, F-410, F-430, F-477, F-510, F-551, F-552, F- 553, F-554, F-555, F-556, F-557, F-558, F-559, F-560, F-561, F-562, F-56 3, F-565, F-568, F-569, F-570, F-574, F-575, F-576, R-40, R-40-LM, R-41, R-94, RS-56, RS-72-K, RS-75, RS-76-E, RS-76-NS, RS-78, RS-90, DS-21 (DIC Sun Chemical);KY-164, KY-108, KY-1200, KY-1203 (Shin-Etsu Chemical Co., Ltd.);Dowsil 14, Dowsil 11, Dowsil 54, Dowsil 57, Dowsil FZ2110, FZ-2123;Xiameter OFX-0077;ECOSURF EH-3, EH-6, EH-9, EH-14, SA-4, SA-7, SA-9, SA-15; Tergitol 15-S-3, 15-S-5, 15-S-7, 15-S-9, 15-S-12, 15-S-15, 15-S-20, 15-S-30, 15-S-40, L61, L-62, L-64, L-81, L-101, XD, XDLW, XH, XJ, TMN-3, TMN-6, TMN-10, TMN-100X, NP-4, NP-6, NP-7, NP-8, NP-9, NP-9.5, NP-10, NP-11, NP-12, NP-13, NP-15, NP-30, NP-40, NP-50, NP-70; CF-10, CF-21, CF-32, CF76, CF87, DF-12, DF-16, DF-20, GR-7M, BG-10, CG-50, CG-110, CG-425, CG-600, CG-650, CA, N-57, X-207, HW 1000, RW-20, RW-50, RW-150, X-15, X-35, X-45, X-114, X-100, X-102, X-165, X-305, X -405,X-705;PT250,PT700,PT3000,P425,P1000TB,P1200,P2000,P4000,15-200(Dow Chemical);DC ADDITIVE 3, 7, 11, 14, 28, 29, 54, 56, 57, 62, 65, 67, 71, 74, 76, 163(Dow Silicones); TEGO Flow 425, Flow 370, Glide 100, Glide 410, Glide 415, Glide 435, Glide 432, Glide 440, Glide 450, Flow 425, Wet 270, Wet 500, Rad 2010, Rad 2200 N, Rad 2011, Rad 2250, Rad 2500, Rad 2700, Dispers 670, Dispers 653, Dispers 656, Airex 962, Airex 990, Airex 936, Airex 910(Evonik); BYK-300, BYK-301 / 302, BYK-306, BYK-307, BYK-310, BYK-315, BYK-31 3, BYK-320, BYK-322, BYK-323, BYK-325, BYK-330, BYK-331, BYK-333, BYK-337, BYK-3 41, BYK-342, BYK-344, BYK-345 / 346, BYK-347, BYK-348, BYK-349, BYK-370, BYK-375 , BYK-377, BYK-378, BYK-UV3500, BYK-UV3510, BYK-UV3570, BYK-3550, BYK-SILCLEAN 3700, Modaflow® 9200, Modaflow® 2100, Modaflow® Lambda, Modaflow® Epsilon, Modaflow® Resin, Efka FL, Additiol XL 480, Additol XW 6580, and BYK-SILCLEAN 3720;
[0094] In some non-limiting embodiments, the leveling agent can be present in an amount of 0-1 wt%, or 0.001-0.9 wt%, or 0.05-0.5 wt%, or 0.05-0.25 wt%, or 0.05-0.2 wt%, or 0.1-0.15 wt%.
[0095] The photolithographic liquid composition of the present disclosure can be prepared by combining one or more polymers of the present disclosure, any organic solvent, water or additional components, and a photoactive compound as a curing agent in any order. The organic solvent is the same as described above. When the present composition contains a photoactive compound such as diazonaphthoquinone, onium salt, or photoinitiator, it is preferred that the curing agent is first dissolved in a suitable organic solvent or alkaline aqueous solution, then mixed with one or more of the present polymers and any optional surfactant, and then mixed with any optional adhesion promoter. The selection of a suitable photoactive compound is within the ordinary level of a person skilled in the art.
[0096] In some embodiments, the liquid composition of the present disclosure can be coated or deposited on a substrate by any suitable method. The substrate can be the same as described above. Suitable methods for coating the composition can include, but are not limited to, spin coating, curtain coating, spray coating, roller coating, dip coating, vapor deposition, and lamination such as vacuum lamination and hot roll lamination, among other methods. In the semiconductor manufacturing industry, spin coating is a preferred method to utilize existing equipment and processes. In spin coating, the solid content of the composition can be adjusted along with the spin speed to achieve the desired thickness of the composition on the surface to be applied.
[0097] If the liquid composition of the present disclosure does not contain an adhesion promoter, the surface of the substrate to be coated with the composition can be optionally contacted with a suitable adhesion promoter or vapor-treated first.Various vapor treatments known in the art, such as plasma treatment, can enhance the adhesion of the polymer of the present disclosure to the substrate surface.In certain applications, it may be preferable to treat the substrate surface with an adhesion promoter before coating the surface with the composition.The adhesion promoter is the same as that described above.
[0098] Typically, the liquid composition of the present disclosure is spin-coated at a spin speed of 400-4000 rpm. The amount of the composition dispensed onto the wafer or substrate depends on the total solids in the composition, the desired thickness of the resulting layer, and other factors well known to those skilled in the art. When a film or layer of the composition is cast by spin-coating, much (or all) of the solvent evaporates during deposition of the film. Preferably, after being deposited on the surface, the composition is heated (soft-baked) to remove any residual solvent. Typical baking temperatures are 90-120° C., although other temperatures may be suitably used. Such baking to remove residual solvent is typically performed for approximately 1 or 2 minutes, although longer or shorter times may be suitably used.
[0099] The resin composition of the present disclosure is typically cured by heating for a period of time. Suitable curing temperatures range from 140 to 300° C., or from 170 to 250° C. Typically, curing times range from 1 to 600 minutes, or from 30 to 240 minutes, or from 30 to 120 minutes.
[0100] Generally, the thickness of the formed resin composition layer is equal to or greater than the thickness of the conductive layer. Since the thickness of the conductive layer of the circuit board is generally within the range of 5 to 70 μm, the resin composition layer generally has a thickness of 10 to 100 μm.
[0101] In one embodiment, a liquid composition comprising a polymer described herein can be spin cast onto copper. The composition can be cast by a slot die coater or other suitable equipment to form a dry film desired for microelectronic applications. The cast film can be soft baked to remove residual solvent at a temperature of 70-150°C, or 90-120°C for 30 seconds to 10 minutes. The soft baked film can then be exposed to cure conditions of 150-250°C for 30 minutes to 4 hours.
[0102] In some embodiments, a layer of the liquid composition of the present disclosure may be formed as a dry film and disposed on the surface of a substrate by lamination. In a lamination-based process where the adhesive film has a protective film with a thickness of 1 to 40 μm, the protective film is first peeled off, and then the adhesive film and the circuit board are preheated as necessary, and the adhesive film is pressed and heated while being bonded to the circuit board. In some non-limiting embodiments, a method is preferably adopted in which the adhesive film is laminated to the circuit board under reduced pressure by a vacuum lamination method. Non-limiting lamination conditions include a bonding temperature (lamination temperature) of 70 to 140° C., a pressure of 1 to 11 kgf / cm 2 (9.8×10 4 ~107.9×10 4 N / m 2 ) and a reduced pressure of 20 mHg (26.7 hPa) or less for air pressure. The lamination method may be a batch type or a continuous type using rolls. Vacuum lamination can be performed using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum applicator manufactured by Nichigo-Morton Co., Ltd., a vacuum pressure laminator manufactured by Meiki Co., Ltd., a roll-type dry coater manufactured by Hitachi Industries Co., Ltd., and a vacuum laminator manufactured by Hitachi AIC Inc.
[0103] The lamination process, which involves heating and pressing under reduced pressure, can be carried out using a general vacuum hot press. For example, the lamination process can be carried out by pressing a heated metal plate such as a SUS plate from the support layer side. Lamination is usually carried out at a rate of 1×10 -2 In some non-limiting embodiments, the pressure is reduced to 1×10 -3 Heating and pressing can be done in one step, but it is usually advantageous to do so in two or more steps to prevent the resin from bleeding. For example, the first pressing step is done at a pressure of 1 to 15 kgf / cm 2The second press can be performed at a pressure of 1 to 40 kgf / cm at a temperature of 70 to 150°C. 2 The pressing can be performed at a pressure of 1000 MPa and a temperature of 150-200° C. In some non-limiting embodiments, pressing is performed for 30-120 minutes at each stage. Examples of commercially available vacuum hot press machines include MNPC-V-750-5-200 (Meiki Co., Ltd.) and VH1-1603 (Kitagawa Seiki Co., Ltd.).
[0104] The insulating layer can be formed on the circuit board by laminating an adhesive film on the circuit board, cooling the laminate to about room temperature, peeling off the support if peeling off the support, and then heat curing the resin composition layer. Appropriate conditions for heat curing can be selected according to the type and content of each resin component in the resin composition disclosed herein. In some non-limiting embodiments, the temperature and time for heat curing are selected from the ranges of 150 to 220°C and 20 to 180 minutes, and in some non-limiting embodiments, the temperature and time for heat curing are selected from the ranges of 160 to 210°C and 30 to 120 minutes.
[0105] After the insulating layer is formed, the support is peeled off if it was not peeled off before curing. Then, holes are drilled in the insulating layer formed on the circuit board as necessary to form via holes or through holes. Drilling can be performed by one or more methods known to those skilled in the art, including, for example, drilling, laser, plasma, etc. In some non-limiting embodiments, drilling is accomplished using a laser, such as a carbon dioxide laser and a YAG laser.
[0106] Subsequently, a conductive layer is formed on the insulating layer by dry plating or wet plating. Non-limiting examples of dry plating methods include vapor deposition, sputtering, and ion plating. In wet plating, the surface of the insulating layer is successively subjected to a swelling treatment with a swelling liquid, a surface roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid, thereby forming an anchor with projections and recesses. The swelling treatment with a swelling liquid can be performed by immersing the insulating layer in the swelling liquid at 50 to 80°C for 5 to 20 minutes. Non-limiting examples of the swelling liquid include an alkaline solution and a surfactant solution. Examples of the alkaline solution include a sodium hydroxide solution and a potassium hydroxide solution. Examples of commercially available swelling liquids include Swelling Dip Securiganth P and Swelling Dip Securiganth SBU (Atotech Japan KK). The surface roughening treatment with an oxidizing agent can be performed by immersing the insulating layer in an oxidizing agent solution at 60 to 80°C for 10 to 30 minutes. Non-limiting examples of the oxidizing agent include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide, dichromate, ozone, hydrogen peroxide / sulfuric acid, and nitric acid. The concentration of permanganate in the alkaline permanganate solution may be about 5 to 10% by weight. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as Concentrate Compact CP and Dosing Solution Securiganth P (Atotech Japan KK). The neutralization treatment with a neutralizing solution can be performed by immersing the insulating layer in a neutralizing solution at 30 to 50°C for 3 to 10 minutes. In some non-limiting examples, the neutralizing solution may be an acidic aqueous solution. Examples of commercially available neutralizing solutions include Reduction Solution Securiganth P (Atotech Japan KK).
[0107] Alternatively, the conductive layer may be formed by forming a plating resist having a reverse pattern of the conductive layer and performing electroless plating only. Subsequent patterning methods may be subtractive or semi-additive methods known to those skilled in the art.
[0108] The present disclosure also relates to a wide variety of electronic devices comprising at least one layer of the dielectric film of the present application on an electronic device substrate. The electronic device substrate can be any substrate for use in the manufacture of any electronic device. Exemplary electronic device substrates include, without limitation, semiconductor wafers, glass, sapphire, silicate materials, silicon nitride materials, silicon carbide materials, display device substrates, epoxy molding compound wafers, circuit board substrates, and thermally stable polymers.
[0109] As used herein, the term "semiconductor wafer" is intended to encompass semiconductor substrates, semiconductor devices, and various packages for various levels of interconnection, such as single chip wafers, multiple chip wafers, packages for various levels, substrates for light emitting diodes (LEDs), or other assemblies requiring solder connections. Semiconductor wafers, such as silicon wafers, gallium arsenide wafers, and silicon germanium wafers, may be patterned or unpatterned. As used herein, the term "semiconductor substrate" includes any substrate having one or more semiconductor layers or structures that include active or operable portions of a semiconductor device. The term "semiconductor substrate" is defined to mean any structure that includes semiconductor material, such as a semiconductor device. A semiconductor device means a semiconductor substrate on which at least one microelectronic device has been or will be fabricated. Thermally stable polymers include, without limitation, any polymers that are stable to the temperatures used to cure arylcyclobutene materials, such as polyimides, e.g., KAPTON™ polyimide (DuPont, Wilmington, DE), liquid crystal polymers, e.g., VECSTAR™ LCP film (Kuraray Co., Ltd., Tokyo, Japan), and bismaleimide-triazine (BT) resin (MGC, Tokyo, Japan). Additional polymer substrates may include polyolefins, such as polyethylene, polypropylene, and polyvinyl chloride; polyester films, such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate; or polycarbonate films. In addition, release paper and metal foils, such as copper foil and aluminum foil, may be used. The support and the protective film described below may be surface-treated, such as matte treatment and corona treatment. Alternatively, the support and the protective film may be release-treated with a release agent, such as a silicone resin-based release agent, an alkyd resin-based release agent, or a fluororesin-based release agent. In some non-limiting embodiments, the support has a thickness of 10 to 150 μm, and in some non-limiting embodiments, 25 to 50 μm. EXAMPLES
[0110] raw materials: Monomers and other components were obtained / prepared as follows: β-myrcene (Vigon), styrene (Sigma Aldrich), vinyl toluene isomer mixture (Deltech Corporation), Vazo65 initiator (Wako Chemical), 4-vinylpyridine (Vertellus, used as received), bismaleimide BMI-689 (Designer Molecules), SPV-100 (Otsuka Chemical Co., Ltd., used as received), spherical silica with average particle size of 0.5 μm ("SC2050-MTM" from Admatechs Company Limited, used as received). Vinylphenoxy BCB [1-(4-vinylphenoxy)benzocyclobutene)] was prepared according to (Patent Document 3), the entire contents of which are incorporated herein by reference. Phenolic resins were obtained from Meiwa Kasei Co., Ltd., DIC Corporation, or Nippon Kayaku Co., Ltd. as appropriate and used as received. All other solvents and chemicals were received from Fisher Scientific and used as received without further purification.
[0111] Molecular weight measurement: Polymer samples were prepared as 0.5 wt% solutions in tetrahydrofuran and filtered through a 0.2 micron Teflon filter. The mobile phase was 0.5% triethylamine, 5% methanol, and 94.5% tetrahydrofuran. The column used was a Waters Styragel HR5E 7.8 x 300 mm column Lot No. 0051370931. The injection volume was 100 microliters and the run time was 27 minutes. Molecular weight data are reported relative to polystyrene standards.
[0112] Preparation and processing of membrane samples: The formulation solution was drawdown coated onto a PET substrate (NANYA NV38G, 38 μm thick) by a steel bar with a 6 mil gap. The film was soft baked at 115° C. for 3 minutes. The film was laminated onto a suitable substrate by a Meiki (MVLP500 / 600) laminator using a first stage vacuum using a rubber contact at approximately 2 hPa with a pressure of 0.95 MPa for 30 seconds and a temperature of 90° C., and a second stage vacuum using a steel plate with a pressure of 1.5 MPa and a temperature of 90° C. for 1 minute. For free-standing film samples, the samples were then cured in a BlueM oven at 180° C. for 1 hour in nitrogen with less than 100 ppm oxygen on a copper substrate. The resulting substrate was cut to the appropriate size, and the film was lifted in 5% ammonium sulfate in water or a water bath, rinsed, and dried to obtain a free-standing film for analysis.
[0113] Test Method (1) Dielectric properties: The dielectric properties of the free-standing membranes were determined using IPC test method TM-650 2.5.5.13 (rev.01 / 07) with a copper split cylindrical resonator machined to have a cavity frequency of 10 GHz each and a Keysight N5224A PNA network analyzer. The membrane geometry was such that the substrate extended beyond the diameter of the two cylindrical cavities. The thickness of the dielectric substrate can vary from 0.01 mm to 5.0 mm, but a substrate thickness of 0.03 mm was used in these studies. The free-standing membrane was placed in the cavity of the split cylindrical resonator and the TE 011 The resonant frequencies and quality factors of the resonant modes were measured using a network analyzer. The dielectric constant (Dk) and loss tangent (Df) of the films were measured using custom software written in MATLAB. 011 Calculated from the resonant modes.
[0114] (2) Thermodynamic and gravimetric analysis: Free-standing films were cut into 10 mm x 25 mm geometries and mounted in a TA Instruments Dynamic Mechanical Analyzer Q800 instrument with a strain rate of 0.06%, a preload of 1 Newton, and a frequency of 1 Hertz. The temperature was equilibrated at 50°C and then increased to 200°C at a rate of 5°C per minute. The maximum of the tan δ curve was taken as the glass transition temperature value. Water absorption was obtained from a thermogravimetric analyzer TA Instruments Q5000SA using the conditions of mass gain at 60°C and 60% relative humidity. Thermomechanical analysis was performed in tensile mode on a TA Instruments Thermomechanical Analyzer Q400. The samples were heated at a constant rate from 5°C to 280°C, then cooled to -50°C, and then returned to 250°C at the same rate. The thermal expansion coefficient was determined as the linear change in dimensions from -25°C to 50°C in the last cycle.
[0115] Peel test (1) Surface roughening treatment Roughening of the substrate surface was achieved by a three-stage desmear procedure. The sample was first immersed in CIRCUPOSIT™ Sweller 7810 available from DuPont de Nemours at 70° C. for 20 minutes. It was then rinsed with a strong water stream for 2 minutes to remove excess swelling agent solution. It was then immersed in CIRCUPOSIT™ MLB Promoter 3308 aqueous permanganate solution available from DuPont de Nemours at 80° C. for variable times. After rinsing with water for 2 minutes, residual promoter deposits were removed by immersing the sample in CIRCUPOSIT™ Neutralizer 216 available from DuPont de Nemours at 40° C. for 5 minutes. After a final rinse with a strong water stream for 2 minutes, the sample was dried in a stream of air. The degree of texturing was determined by measuring the mass difference of the substrate before and after desmearing, normalized by the surface area of the sample.
[0116] (2) Electroless plating The desmeared samples were prepared for electroless deposition by first immersing the substrate in CIRCUPOSIT™ Conditioner 8512 available from DuPont de Nemours for 5 minutes at 40°C, followed by rinsing under a strong water stream for 2 minutes. The samples were then immersed in a 3% aqueous solution of nitric acid at room temperature for 30 seconds. Immediately after, the samples were immersed in CIRCUPOSIT™ 6530 Catalyst available from DuPont de Nemours, an ionic aqueous alkaline palladium catalyst, for 5 minutes at 40°C. The catalyst is buffered with sufficient sodium carbonate, sodium hydroxide, or nitric acid to achieve a catalyst pH of 9-9.5. The samples were then rinsed under a strong water stream at room temperature for 2 minutes. The panels were then immersed in a solution of 0.6 g / L dimethylamine borane and 5 g / L boric acid for 2 minutes at 30°C to reduce the palladium ions to palladium metal, followed by rinsing under a strong water stream for 2 minutes. The activated sample was then immersed in an electroless copper plating bath CIRCUPOSIT™ 6550, available from DuPont de Nemours, for 5 minutes at 35° C. As a result, copper was conformally deposited over the entire sample to a target copper thickness of 0.4 μm. The metallized sample was then rinsed with a strong stream of water and quickly dried with a stream of air. To anneal the electroless copper deposit and remove residual water from the deposit, the sample was rinsed with N 2 A final soft bake was performed at 120° C. for 30 minutes in ambient.
[0117] (3) Electrolytic plating The metallized samples were prepared for electrolytic plating by immersion in RONACLEAN™ LP-200 available from DuPont de Nemours for 1.5 minutes at 35°C. The samples were then rinsed with running water for 2 minutes and residual surface oxides were removed by immersion in 10% aqueous sulfuric acid at room temperature for 30 seconds. The samples were then placed in a Haring cell containing copper electroplating bath MICROVIA™ EVF-II available from DuPont de Nemours as the electrolyte and two insoluble anodes. Solution agitation was provided by bubbling outlets on either side of the sample. Electrolytic plating was performed at 20 ASF for 50 minutes to reach a target plating thickness of 18 μm. Based on a prior analysis of consumption rates in this electrolytic plating setup, brightener plating additives were periodically replenished during plating to maintain initial concentrations. After electrolytic plating was completed, the samples were removed from the Haring cell and rinsed with a strong stream of water. The samples were then immersed in a basic anti-tarnish solution containing benzotriazole to protect the surface from oxidation. 2 The copper deposit was annealed by ambient baking at 180° C. for 1 hour to complete the hardening of the underlying dielectric film.
[0118] (4) Plating peeling test After the plated copper samples were annealed, a 1 centimeter wide peel strip was cut on the specimen using a suitable blade, after which the copper strip was peeled off at a 90 degree angle at a speed of 50 mm / min on an Intron tensile tester. The peel force value (kilogram force / centimeter) was calculated. For samples undergoing highly accelerated stress testing (HAST), the cut specimen was exposed to an atmosphere of 130°C and 85% relative humidity for 50 hours, at which point the same peel test was performed and the value recorded. Values below 0.15 kgf / cm were considered poor and values above 0.15 kgf / cm were considered good.
[0119] Example A1 (Synthesis of arylcyclobutene resin) The following monomers and solvents were charged to a 100 L jacketed reactor with overhead stirring and heated to 79° C. under a nitrogen blanket: 19695.8 g 1-(4-vinylphenoxy)benzocyclobutene, 15090.5 g vinyltoluene, 1517.7 g vinylpyridine, 8445.6 g β-myrcene, and 19178.4 g cyclopentanone. An initiator feed of 1401.1 g V65 and 17131.5 g cyclopentanone was fed at a constant rate to the reactor for 20 hours, and the temperature was held for an additional 3 hours before returning to 40° C. This solution was used directly in the formulation examples. GPC Mn 7.4k, Mw 33.5k
[0120] Example B1 ( Allyl Synthesis of Ether Resin B1) For the synthesis of allyl resin, the following generalized procedure was used: In a 250 ml round bottom flask equipped with a stir bar and reflux condenser under nitrogen blanket, 10 g of MEH-7500 (phenol benzaldehyde copolymer, 110 OH equivalents) from Meiwa Kasei Co., Ltd. was added and dissolved in acetonitrile (40 g, 4 times the mass of the phenolic resin). When dissolution was complete, potassium carbonate (18.85 g, 1.5 equivalents relative to OH equivalents) was added and the resulting slurry was heated to 80° C. for 1 hour. Allyl bromide (8.64 ml, 1.1 equivalents relative to OH equivalents) was then added by syringe over 15 minutes. The mixture was stirred at 80° C. for 16 hours. The solution was then cooled to room temperature, dichloromethane (80 grams, 8 times the mass of the phenolic resin) and water (80 grams, 8 times the mass of the phenolic resin) were added and the mixture was stirred for 1 hour. The mixture was transferred to a separatory funnel where the organic layer was collected, dried over magnesium sulfate (40 grams, 4 times the mass of the phenolic resin), filtered, and the solvent was removed under reduced pressure.
[0121] The B1 product was received as a dark red viscous oil in 87% yield of the expected product. The structure was confirmed by proton NMR using deuterated dimethylsulfoxide as the solvent at 500 MHz field. In comparison to the starting material, the phenol-OH resonances at 9.0-10.0 ppm were no longer detectable, while resonances at 5.9-6.3 ppm (1H), 5.1-5.4 ppm (2H), and 4.3-4.5 ppm (2H) were observed, consistent with a phenolate ether structure. [ka]
[0122] Example B2 ( Allyl Synthesis of Ether Resin B2 The same procedure as in Synthesis Example B1 was used, except that TD-2090 from DIC Corporation was used (phenol formaldehyde copolymer) with a phenol equivalent weight of 105. NMR detection was performed in the same manner as in Example B1, and gave results consistent with a phenolate ether structure. The material was isolated as a red viscous oil in 86% yield. [ka]
[0123] Example B3 ( Allyl Synthesis of Ether Resin B3) The same procedure as in Synthesis Example B1 was used, except that GPH-103 (biphenyl / phenol formaldehyde copolymer) from Nippon Kayaku Co., Ltd., with a phenol equivalent weight of 232, was used. NMR detection was performed in the same manner as in Example B1, and gave results consistent with a phenolate ether structure. The material was isolated as a light pink viscous oil in 89% yield. [ka]
[0124] Example B4 ( Allyl Synthesis of Ether Resin B4) The same procedure as in Synthesis Example B1 was used, except that VH-4170 (bisphenol-A formaldehyde copolymer) from DIC Corporation with a phenol equivalent weight of 232 was used. NMR detection was performed in the same manner as in Example B1, and gave results consistent with a phenolate ether structure. The material was isolated as a colorless viscous oil in 95% yield. [ka]
[0125] Example B5 ( Allyl Synthesis of Ether Resin B5) The same procedure as in Synthesis Example B1 was used, except that KA-1163 (cresol formaldehyde copolymer) from DIC Corporation with a phenol equivalent weight of 118 was used. NMR detection was performed in the same manner as in Example B1, and gave results consistent with a phenolate ether structure. The material was isolated as a light pink viscous oil in 91% yield. [ka]
[0126] Example B6 ( Allyl Synthesis of Ether Resin B6) The same procedure as in Synthesis Example B1 was used, except that MEH-7000 (naphthalene / phenol formaldehyde copolymer) from Meiwa Kasei Co., Ltd., with a phenol equivalent weight of 145 was used. NMR detection was performed in the same manner as in Example B1, and gave results consistent with a phenolate ether structure. The material was isolated as a dark red viscous oil in 81% yield. [ka]
[0127] Example B7 (Synthesis of Comparative Phenolate Methacrylate Resin B7) In a 250 ml round bottom flask equipped with a stir bar and reflux condenser under nitrogen blanket, 10 g of DL-92 (phenol formaldehyde copolymer, 109 OH equivalents) from Meiwa Kasei Co., Ltd. and 0.56 g of dimethylaminopyridine (0.05 equivalents relative to OH equivalents) were added and dissolved in dichloromethane (20 g, 2 times the mass of the phenolic resin). When dissolution was complete, methacrylic anhydride (19.54 ml, 1.15 equivalents relative to OH equivalents) was added by syringe and the resulting mixture was stirred at room temperature for 16 hours. Then, dichloromethane (80 grams, 8 times the mass of the phenolic resin) and saturated aqueous sodium bicarbonate solution (200 grams, 20 times the mass of the phenolic resin) were added to the separatory funnel with the reaction mixture. The funnel was shaken and the layers were then allowed to separate. The organic layer was collected, dried over magnesium sulfate (40 grams, 4 times the mass of the phenolic resin) and filtered. Residual solvent was removed under reduced pressure. The product was received as a red viscous oil in 95% yield of the expected product.
[0128] The structure was confirmed by proton NMR using deuterated dimethylsulfoxide as the solvent at a field of 500 MHz. In comparison to the starting material, the phenol-OH resonances at 9.0-10.0 ppm were no longer detectable, while resonances at approximately 6.3 ppm (1H), approximately 6.0 ppm (1H), and approximately 2.0 ppm (3H) were observed, consistent with a phenolate methacrylate structure. The material was isolated as a colorless viscous oil in 95% yield. [ka]
[0129] Example B8 (Synthesis of Comparative Phenolate Vinyl Benzyl Resin B8) The same procedure as in Synthesis Example B1 was used, except that DL92 (phenol formaldehyde copolymer) from Meiwa Kasei Co., Ltd. with a phenol equivalent weight of 109 was used, and vinylbenzyl chloride was used instead of allyl bromide. NMR detection of the structure confirmed the disappearance of the phenol OH peak and the appearance of broad resonances at about 6.7 ppm (1H), about 5.8 ppm (1H), about 5.3 ppm (1H), and about 5.0 ppm (2H), consistent with a phenolate vinylbenzyl structure. The material was isolated as a dark red viscous oil in 91% yield. [ka]
[0130] Example B9 (Synthesis of Comparative Methacrylic Acid Ester Resin B9) The same procedure as in synthesis example B7 was used, except that MEH-7500 (phenol-benzaldehyde copolymer) from Meiwa Kasei Co., Ltd. with a phenol equivalent weight of 110 was used. NMR detection was performed using the same procedure as in example B7, and the results were consistent with a methacrylate ester structure. The material was isolated as a red viscous oil in 95% yield. [ka]
[0131] Example B10 (Synthesis of Comparative Resin B10) The synthesis of the adduct of benzocyclobutene carboxylic acid chloride and Neaollyl P30 was carried out according to (Patent Document 4). [ka]
[0132] Formulations and film preparation (1) Formulation and Film Example 1 A 20 ml glass vial was charged with 72 parts of benzocyclobutene resin A1, 18 parts of allyl resin B1, 7 parts of flame retardant C1 SPV-100 from Otsuka Chemical Co., Ltd., 2 parts of softener D1 BMI-689 from Designer Molecules Inc., 0.35 parts of surfactant E1 Modaflow® resin from Allnex, 224 parts of methacrylic acid functionalized spherical silica SC2050-MTM from Admatechs Company Limited, and volatile components 96 parts of 2-butanone G1 and 83 parts of cyclopentanone G2. The mixture was rocked overnight to mix, after which the resulting solution was used to prepare a membrane as described herein for evaluation.
[0133] (2) Formulations and Films Examples 2 to 9 and Comparative Examples 1 to 4 Formulations and membrane examples 2-9 and comparative examples 1-4 were prepared using procedures similar to those described for Example 1 with the compositions listed in Table 1. The corresponding membrane test data are shown in Table 2.
[0134] [Table 1]
[0135] [Table 2]
[0136] All resin formulations have dielectric constants (D k ) and dielectric loss (D f ), but only those formulations containing a second resin with an allyl group result in films with plating peel strengths high enough to make them practically useful. Furthermore, the proper selection of the allyl-based second monomer can be used to f This can result in a decrease in
[0137] It should be noted that not all of the acts described above in the summary or examples are required, that some of the specific acts may not be required, and that one or more additional acts may be performed in addition to those described. Furthermore, the order in which the acts are listed is not necessarily the order in which the acts are performed.
[0138] In the foregoing specification, the concepts have been described with reference to specific embodiments. However, those skilled in the art will recognize that various modifications and changes can be made without departing from the scope of the present disclosure as set forth in the following claims. Accordingly, the specification and drawings are to be regarded in an illustrative rather than a restrictive sense, and all such modifications are intended to be included within the scope of the present disclosure.
[0139] Benefits, other advantages, and solutions to problems have been described above with respect to particular embodiments. However, the benefits, advantages, solutions to problems, and any features that may give rise to or make more prominent any benefit, advantage, or solution should not be construed as critical, required, or essential features of any or all claims.
[0140] It should also be appreciated that, for clarity, certain features are described herein in the context of separate embodiments, and may be provided in combination in a single embodiment. Conversely, for brevity, various features described in the context of a single embodiment may also be provided individually or in any subcombination. The use of various ranges of numerical values set forth herein is described as approximations, as if the minimum and maximum values within the stated ranges were both preceded by the word "about". In this format, slight variations above and below the stated ranges may be used to achieve substantially the same results as the values within the ranges. Also, the disclosure of these ranges is intended to be continuous ranges including every value between the minimum and maximum average values, including fractional values that may occur when some of the components of one value are mixed with components of a different value. Furthermore, when broader and narrower ranges are disclosed, it is within the expectation of the present disclosure to match the minimum value from one range with the maximum value from another range, and vice versa. The present invention includes the following aspects 1 and 2. [Aspect 1] (a) 60 to 90% by weight of at least one thermosetting resin; (b) a resin composition comprising a mixture containing 10 to 40% by weight of at least one allyl ether resin. [Aspect 2] 2. The resin composition of claim 1, wherein the thermosetting resin is an arylcyclobutene resin.
Claims
1. A resin composition comprising a mixture comprising: (a) 60 to 90% by weight of at least one thermosetting resin; and (b) 10 to 40% by weight of at least one allyl ether resin, the thermosetting resin is an arylcyclobutene resin, The arylcyclobutene resin is (a) 10 to 50 mole % of one or more addition polymerizable arylcyclobutene monomers; (b) 15 to 60 mol % of one or more dienophile monomers, (c) 15 to 50 mol % of one or more diene monomers, and (d) 0 to 10 mol % of one or more heterocycle-containing monomers; The polymerization product from a mixture comprising The one or more addition polymerizable arylcyclobutene monomers are represented by formula (A-1-a) and formula (A-2-a): 【Chemistry 1】 wherein Ar is a substituted or unsubstituted carbocyclic arylene or a substituted or unsubstituted heteroarylene group; Q is a covalent bond, O, S, or NR a , where R a is selected from the group consisting of hydrogen, deuterium, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl, R 5 to R 7 are the same or different and are independently selected from the group consisting of hydrogen, deuterium, alkyl, alkoxy, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl, R 8 is selected from the group consisting of alkyl, alkoxy, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl, and a is an integer from 0 to 4. 【Chemistry 2】 wherein Ar is a substituted or unsubstituted carbocyclic arylene or a substituted or unsubstituted heteroarylene group; Q is a covalent bond, O, S, or NR a ; R a is selected from the group consisting of hydrogen, deuterium, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl; R 1 to R 7 are the same or different and are independently selected from the group consisting of hydrogen, deuterium, alkyl, alkoxy, aryloxy, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl; R 8 is selected from the group consisting of alkyl, alkoxy, substituted or unsubstituted carbocyclic aryl, and substituted or unsubstituted heteroaryl; and b is an integer from 0 to 3. having a structure selected from the group consisting of: The one or more dienophile monomers are represented by formula (II) 【Chemistry 3】 wherein B is hydrogen, substituted or unsubstituted alkyl, substituted or unsubstituted aromatic, substituted or unsubstituted heteroaromatic, substituted or substituted alkyloxy, or hydroxy; R 9 to R 11 are the same or different and are independently selected from the group consisting of hydrogen, vinyl, allyl, substituted or unsubstituted isoprene having 5 to 100 carbon atoms, substituted or unsubstituted alkyl groups having 1 to 100 carbon atoms, halogen, cyano, substituted or unsubstituted aryl groups having 6 to 100 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 100 carbon atoms, and combinations thereof. and having a structure given by The one or more diene monomers are represented by formula (IV): 【Chemistry 4】 wherein R 16 is the same or different and is independently selected from the group consisting of hydrogen and methyl; R 17 is the same or different and is independently selected from the group consisting of hydrogen, C 1-5 alkyl, C 1-5 alkoxy, C 1-5 thioalkyl, and C 5-12 alkenyl. and having a structure given by the one or more heterocycle-containing monomers are selected from the group consisting of vinyl-substituted C 3-12 heterocycles and vinyl-substituted C 3-5 heterocycles; The at least one allyl ether resin is represented by the formula (B1) to (B6) 【Chemistry 5】 【Chemistry 6】 (Wherein, n=1 to 10) A resin composition selected from the group consisting of:
2. A liquid composition comprising the resin composition according to claim 1 and one or more solvents.
Citation Information
Patent Citations
Phenolic resin and epoxy resin composition and maleimide resin composition comprising the same
JP1994192361A
Printed wiring board, method of manufacture thereof and article comprising the same
JP2020150263A
Polymeric resin for dielectric applications
JP2021109965A
US10,030,165B2
Methods of making stable and thermally polymerizable vinyl, amino or oligomeric phenoxy benzocyclobutene monomers with improved curing kinetics
US20190169327A1